Blood Vitamin D Levels in Hypercholesterolemic Patients - Hermawan, Dessy; Muhani, Nova; Arisandi, Syafik (Universitas Aisyah Pringsewu, 2022)
The prevalence of hypercholesterolemia in Indonesia is currently still high, even though hypercholesterolemia is correlated with non-communicable diseases such as hypertension, heart disease, diabetes mellitus and so on. Recent studies have reported an association between low levels of vitamin D and increased cholesterol levels. This is interesting, if it is true that vitamin D is related to cholesterol levels, then people who live in tropical areas like Indonesia, should have low cholesterol levels. The purpose of this study was to analyze the relationship between vitamin D levels and total cholesterol levels in medical students of Malahayati University class of 2017. The design of this research is an analytical survey with a case-control approach. The case sample was a total of medical students class 2017 who suffered from hypercholesterolemia as many as 26 people. The control sample was 26 students who had normal cholesterol levels, so the total sample was 52 students. The results showed that there were a significant relationship between cholesterol levels and blood vitamin D levels (0.005), Body Mass Index/BMI (0.001), waist circumference (0.005), exercise regularity (0.016) and outdoor activity habits (0.001). Suggestion: it is necessary to maintain vitamin D levels in the blood by consuming foods containing vitamin D and being active and exercising outdoors to be exposed to ultraviolet B rays from the sun.Abstrak: Prevalensi hiperkolesterolemia di Indonesia, saat ini masih tinggi, padahal hiperkolesterolemia berkorelasi dengan penyakit tidak menular seperti hipertensi, penyakit jantung, diabetes mellitus dan sebagainya. Penelitian terbaru melaporkan adanya hubungan antara rendahnya kadar vitamin D dengan peningkatan kadar kolesterol. Hal ini menarik, jika benar vitamin D berhubungan dengan kadar kolesterol, maka seharusnya orang-orang yang tingggal di daerah tropis seperti Indonesia, akan memiliki kadar kolesterol yang rendah. Tujuan penelitian ini adalah untuk memperlajari hubungan antara kadar vitamin D dengan kadar kolesterol total pada mahasiswa kedokteran Universitas Malahayati angkatan 2017. Design penelitian ini adalah survey analitik dengan pendekatan case control. Adapun sampel kasus adalah total mahasiswa kedokteran angkatan 2017 yang mengalami hiperkolesterolemia sebanyak 26 orang dan yang menjadi sampel kontrol adalah 26 mahasiswa yang memiliki kadar kolesterol normal, sehingga total sampel sebanyak 52 orang. Hasil penelitian menunjukkan adanya hubungan yang bermakna antara kadar kolesterol dengan kadar vitamin D (0.005), Indeks Massa Tubuh/IMT (0.001), lingkar perut (0.005), keteraturan olah raga (0.016) dan kebiasaan beraktifitas di luar ruangan (0.001). Sedangkan jenis kelamin dan besaran uang jajan tidak berhubungan secara bermakna dengan kadar kolesterol. Saran: perlu menjaga kadar vitamin D dalam darah dengan mengkonsumsi makanan mengandung vitamin D dan berakatifitas serta berolah raga di luar ruangan agar terpapar sinar ultraviolet B dari sinar matahari.